AN ANALYSIS OF DEICTIC EXPRESSION IN THE ARTICLE SELECTED FROM DETIKNEWS ABOUT KRAKATOA’S MOUNT DISASTER 2018 - Yulistiani, Desty; Parmawati, Aseptiana (PROJECT (Professional Journal of English Education), 2020)
This research reports the findings of an investment study deixis in an article selected from DetikNews. The aims of this research was to determine the deictic expression contained in the selected article. The methodology used by the researchers is descriptive qualitative and uses content analysis to analyze deictic expressions in the article. These findings of research indicate are three types of deictic expressions found in articles selected from DetikNews, there are personal deixsis, spatial deixis and temporal deixis. Based on the results of the research, it can be found that knowing the deictic expression in the selected article, this will help all those who read the article, will have a better understanding and the points of the article will reach the audience. Keywords: Deixis , DetikNews